Digital finance, green finance and social finance: Is there a link? - Peterson K. Ozili (Financial Internet Quarterly, 2021)
Identifying the intersection between digital finance, green finance and social finance is important for promoting sustainable financial, social and environmental development. This paper suggests a link between digital finance, green finance and social finance. Using a simple conceptual model, I show that digital finance offers a smooth, efficient and seamless channel for individuals and corporations to fund social projects that deliver a social dividend, and green projects lead to a sustainable environment. The implication is that digital finance is both an enabler and a channel for efficient green financing and social financing.
Keywords: G20; G30; O30; O31; O33; O35; Q01; 330; green finance; social finance; digital finance; sustainable development; environment; sustainable finance; innovation